Effectiveness of water sensitive urban design in storm water management :case study of Sarawak urban catchment, Bau catchment area - Adnan, b Bausah (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Water Sensitive Urban Design (WSUD) has been introduced as Best Management Practices in managing the urban runoff problems, in term of quantity and quality cause by the changing of ground surface conditions due to development activities. In term of runoff quantity, the aim of WSUD is to make sure that the peak discharge from post-development area is same or less compared to the pre-development.